Analysis and statistical projection of vehicle occupancy using average annual daily traffic in the city. (July 2020) - Prada Botía, G C; Rojas-Suárez, J P; Orjuela Abril, M S
Abstract: The excess of both private and public vehicles has hindered the mobility of large cities and, likewise, has begun to affect small cities, increasing environmental pollution, accidents, mortality, among others. The following research work includes the diagnosis and projection to the year 2021 of the traffic generated in the road corridor for future constructions in the adjacent area of the tennis club of the city of "San José de Cúcuta, Colombia", through the collection of data by capacity of vehicles, traffic counts, surveys and vehicle registration, determining the present and future annual average daily traffic, within the main findings it was found that this sector is mostly traveled by cars, trucks and taxis. It was determined that the flow of vehicles will increase in the year 2021 by 24.62%, the constructions of shopping centers will be executed within the sector.